2006
DOI: 10.1002/esp.1458
|View full text |Cite
|
Sign up to set email alerts
|

Badland dynamics in the Central Pyrenees: temporal and spatial patterns of weathering processes

Abstract: The genesis and development of badlands is controlled by bedrock lithology, topography and climate. The development of badlands in the Central Spanish Pyrenees is favoured by the presence of marls and a climate with a marked seasonality; the combination of these factors results in active hydrosedimentological processes. The aim of the present work was to study the dynamics of badlands in the Central Pyrenees, with a focus on the temporal and spatial patterns of the dominant weathering processes. The study area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
2
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 39 publications
4
77
2
6
Order By: Relevance
“…These studies have shown that badland systems developed on Eocene marls constitute the main sediment sources in the Central Pyrenees, with important consequences for siltation of reservoirs (Valero-Garcés et al, 1999). In the Spanish Pyrenees a combination of favorable relief and climatic conditions is coupled with highly erodible marl outcrops, explaining the presence of badland systems with intense soil erosion processes (Regüés et al, 1995;Gallart et al, 2002;Nadal-Romero et al, 2007Alatorre and Beguería, 2009). (Table 6).…”
Section: Major Sediment Sources In the Barasona Watershedmentioning
confidence: 99%
“…These studies have shown that badland systems developed on Eocene marls constitute the main sediment sources in the Central Pyrenees, with important consequences for siltation of reservoirs (Valero-Garcés et al, 1999). In the Spanish Pyrenees a combination of favorable relief and climatic conditions is coupled with highly erodible marl outcrops, explaining the presence of badland systems with intense soil erosion processes (Regüés et al, 1995;Gallart et al, 2002;Nadal-Romero et al, 2007Alatorre and Beguería, 2009). (Table 6).…”
Section: Major Sediment Sources In the Barasona Watershedmentioning
confidence: 99%
“…The geomorphological term 'badland' belongs to unique uncovered and shredded landscapes with steep slopes and high erosion rates being inappropriate for any kind of agricultural use (Nadal-Romero et al 2007;Caraballo-Arias et al 2015;Pintér et al 2015). Geological and mainly the lithological factors have the main influence on the evolution of these landforms (FarabegoliAgostini 2000;Neugirg et al 2016) since the occurrence of badlands is significant on soft materials (Caraballo-Arias et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, few studies focus on potential shifts in the statistical distribution of daily precipitation series (e.g., Durman et al 2001;Christensen 2003, 2004;Frei et al 2003Frei et al , 2006Ekström et al 2005;Boroneant et al 2006;Beniston 2006;Beniston et al 2007). Daily precipitation is closely related to the frequency, magnitude, and duration of droughts and the occurrence of floods and associated geomorphic processes such as erosion and the initiation of landslides (Easterling et al 2000;Nadal-Romero et al 2007). Moreover, changes in the probability distribution of daily rainfall have an effect on runoff generation (MartinVide 2004), potentially either reinforcing or counteracting the impact of climate change on the availability of water resources.…”
Section: Introductionmentioning
confidence: 99%